15.5: Invited Paper: High Performance Autostereoscopic 2D/3D Switchable Display Using Liquid Crystal Lens. Issue 1 (1st July 2013) - Oka, Shinichiro; Naganuma, Tomohiko; Koito, Takeo; Yang, Yingbao; Komura, Shinichi
Abstract We investigated an autostereoscopic 3D display using a Liquid Crystal Gradient Refractive Index (LC GRIN) lens, called LCL (Liquid Crystal Lens) 3D display. The characteristics of the LCL 3D display are high luminance and switchable 2D and 3D images by switching between the states of lens and non‐lens. The LCL 3D display does not influence the 2D image quality. However, the crosstalk of the LCL 3D display is relatively high compared with other methods used in autostereoscopic 3D displays, such as barrier type, lenticular type, and so on. Therefore, we have investigated the reduction of crosstalk for the LCL 3D display.